Asymmetric Subcellular mRNA Distribution Correlates with Carbonic Anhydrase Activity in Acetabularia acetabulum - Serikawa, Kyle A. (American Society of Plant Physiologists, 2001)
The unicellular green macroalga Acetabularia acetabulum L. Silva is an excellent system for studying regional differentiation within a single cell. In late adults, physiologically mediated extracellular alkalinity varies along the long axis of the alga with extracellular pH more alkaline along the apical and middle regions of the stalk than at and near the rhizoid. Respiration also varies with greater respiration at and near the rhizoid than along the stalk. We hypothesized that the apical and middle regions of the stalk require greater carbonic anhydrase (CA) activity to facilitate inorganic carbon uptake for photosynthesis. Treatment of algae with the CA inhibitors acetazolamide and ethoxyzolamide decreased photosynthetic oxygen evolution along the stalk but not at the rhizoid, indicating that CA facilitates inorganic carbon uptake in the apical portions of the alga. To examine the distribution of enzymatic activity within the alga, individuals were dissected into apical, middle, and basal tissue pools and assayed for both total and external CA activity. CA activity was greatest in the apical portions. We cloned two CA genes (AaCA1 and AaCA2). Northern analysis demonstrated that both genes are expressed throughout much of the life cycle of A. acetabulum. AaCA1 mRNA first appears in early adults. AaCA2 mRNA appears in juveniles. The AaCA1 and AaCA2 mRNAs are distributed asymmetrically in late adults with highest levels of each in the apical portion of the alga. mRNA localization and enzyme activity patterns correlate for AaCA1 and AaCA2, indicating that mRNA localization is one mechanism underlying regional differentiation in A. acetabulum.